Grau de conhecimento dos cirurgiões-dentistas sobre odontologia hospitalar - Wayama, Marcelo Tadahiro; Aranega, Alessandra Marcondes [UNESP]; Bassi, Ana Paula Farnezi [UNESP]; Ponzoni, Daniela [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (Associacao Brasileira de Odontologia Rio de Janeiro (ABORJ), 2014)
The aim of this research was to investigate the knowledge, judgment, monitoring and execution of the dentists regarding Hospital Dental Care. Five hundred dentists from Araçatuba (São Paulo state) answered a questionnaire. The results showed that 49% of professionals have never had experience at hospitals and 64% affirmed that this content is poorly approached in graduation. Also 46% of respondents have no interest or don’t think necessary acting in a hospital and 24% believe that this care is done by specialists only. It can be suggested that there is a lack of knowledge about Hospital Dental Care, thus the dentist shall be instructed since academic training for insertion into the hospital team.

O objetivo desta pesquisa foi analisar o conhecimento, opinião, acompanhamento e a execução do cirurgião-dentista na Odontologia Hospitalar. Foram aplicados 500 questionários a cirurgiões-dentistas na cidade de Araçatuba do estado de São Paulo. Os resultados demonstraram que 49% dos profissionais nunca tiveram a experiência no âmbito hospitalar e 64% afirmaram que este conteúdo é carente como parte integrante do currículo de graduação. Outro resultado foi de que 46% dos entrevistados não têm interesse ou não acham necessário atuar dentro do hospital e 24% acreditam que esse atendimento seja feito somente por especialistas. Pode-se sugerir que há carência de conhecimento sobre Odontologia Hospitalar, assim o cirurgião-dentista deve ser instru- ído desde a sua formação acadêmica para a inserção na equipe hospitalar.
Level of knowledge of dentists about hospital dental care
Keywords: Knowledge; Dentistry; Hospital; Conhecimento; Odontologia; Hospital